Complexos de metais de transição: aplicações no tratamento e diagnóstico da doença de Alzheimer - Lima, Márcia Valéria Silva (Universidade Federal de São Carlos, 2014)
Currently there are about 35.6 million people diagnosed with Alzheimer's disease (AD) in the world, and it is expected that this number will double by 2050. Causes of Alzheimer's disease are not yet known, but their symptoms are characterized the decline of cognitive function result of overactivity of the enzyme acetylcholinesterase (AChE); and accumulation of β-amyloid peptide (β-A) in the brain of patients. Therefore it is important to the development of drugs that act on the two problems of AD; cognitive decline (inhibition of AChE activity) and the identification of fibrillar aggregates of β-A (creation of new probes). For this purpose have been prepared and tested a series of luminescent complex; cis-[Ru(phen)2(4- ImAC)]PF6, cis-[Ru(phen)2(4-ImAAc)]PF6, cis-[Ru(phen)2(2-Apy)](PF6)2, where phen = 1,10-phenanthroline, ImAA = 4-imidazole acetic acid, ImAC = 4-imidazole carboxylic acid and Apy = 2-aminopyridine. The ruthenium complexes were synthesized, where its structural elucidation and purity were checked by NMR H1 spectroscopy and by microanalysis. The compounds are soluble in aqueous solutions and exhibit an intense and broad absorption and emission in the visible region. The complexes have relatively long life with 1 the order of 100 ns. The complexes showed moderate inhibition against the enzyme AChE, with an IC50 of about 10-20 μmol.L-1. From the images from confocal microscopy was possible to make the location of the complex inside the cells by luminescent emission, where the imidazole compounds were located specifically in the cytoplasmic portion of the cell, unlike the complex with aminopyridine, which was distributed homogeneously throughout cellular portion. It was possible to identify the formation of fibers from measurements of emission of the luminescent complex, since these complexes have intensity of luminescence variable with different types of Aβ aggregation. The fibrils were also confirmed by fluorescence microscopy emission lifetime. From the results of the complexes exhibit high pharmacological potential to the treatment of AD since they can be used in diagnosis (identification of the fibrils) and in the treatment of AD (AChE inhibition).
Transition metal complex as precursors for bioactive molecules: applications in the treatment of alzheimer's disease
Keywords: Química inorgânica; Complexos de rutênio; Fármacos; Alzheimer; Doença de Alzheimer; Chemistry inorganic; Ruthenium complexe; Drugs; Alzheimer; Alzheimer's disease; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA